X-Day Curriculum as an Independent Learning Curriculum Model At SMA Plus Muthahhari Bandung - Kesi, Mastur Thoyib; Suhifatullah, M. I (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Traditional curriculum in Indonesia often need more flexibility in accommodating students' interests and talents, resulting in limited opportunities for students to explore their skills and creativity. SMA Plus Muthahhari Bandung implements the X-Day Curriculum to create an independent and interest-based learning model, where students can choose areas of interest such as art, language, or sports. This study aims to analyze the implementation of the X-Day Curriculum as a curriculum model that supports independent learning and the development of students' interests and talents. Data was collected through a qualitative approach through in-depth interviews, observation, and documentation analysis. The research was conducted through several technical stages, including data collection, validation, analysis, and interpretation of results. The results showed that the X-Day Curriculum gives students the freedom to choose areas of interest consisting of arts, languages, and sports, facilitating the development of independence, creativity, and life skills relevant to the needs of the 21st century. The program also encourages motivation to learn with a more flexible approach to fun learning, including annual activities such as AKBARI, which appreciates students' work. The study concluded that the X-Day Curriculum effectively shapes students who are independent, innovative, and ready to face future educational challenges.